Measuring the effective levels of company taxation in the New Member States a quantitative analysis - Finkenzeller, Martin; Spengel, Christoph 1964- (Taxation papers / European Commission, Directorate-General Taxation & Customs Union, 2004)
Recoge: 1.Introduction - 2.Methodology and theorical framework - 3.Corporate taxation in the new member states - 4.Effective tax burdens on domestic investments in the new member states - 5.Effective tax burdens on german outbound investments to the new member states.